Stakeholders' Perspectives on the Current State and Transition to Sustainable Soil Management Across Europe - Pulido‐Moncada, Mansonia; Stone, Tiffanie Faye; Bach, Jonna Løvlund; Thorsøe, Martin Hvarregaard; Munkholm, Lars J.; Baratella, Valentina; Vanino, Silvia; Farina, Roberta; Chenu, Claire; Cornu, Sophie; Mason, Eloïse; Keesstra, Saskia; et al. (Wiley-Blackwell, 2025)
Implementing sustainable soil management practices to enhance soil health is a priority in research and policymaking across Europe. There is a need to identify the main soil challenges faced by different European stakeholders and the critical threats limiting the adoption of sustainable management of agricultural soils. The present study analyses stakeholders' perspectives on key soil challenges, knowledge gaps, and priorities for agricultural soil research across partner countries that participated in the European Joint Programme on Soil (EJP SOIL) 2020–2025. Two complementary stakeholder activities—a survey and a workshop—were conducted across 24 partner countries (divided into four regions: Central, Northern, Southern, and Western Europe) of the EJP SOIL consortium in 2024. Among 10 pre-identified soil challenges, the findings highlight that maintaining or increasing soil organic carbon, avoiding soil sealing, and avoiding soil erosion are the top three priorities across Europe. However, the perceived prioritisation of soil challenges differed both between and within regions, reflecting each country's specific soil health context. Divergences in perceptions between practitioners and other stakeholder groups underscore the need to develop actions aimed at better understanding the rationale behind such discrepancies and how to overcome them. In addition, other key challenges for achieving sustainable soil management across Europe include limited funding, policy incoherencies, poor knowledge dissemination and co-creation, and insufficient soil monitoring. Environmental factors influencing soil health, including climate change, together with governance and economic models, were perceived to be critical limitations to the adoption of sustainable management of agricultural soils. This study also emphasises the need for a diversity of engagement methods, policies, and system approaches to support a transition towards sustainable soil management. These findings underscore the need for future research agendas that focus on integrated knowledge and participatory approaches, and strategies involving societal awareness and policy alignment—key elements that have also informed broader strategies involving societal awareness and engagement towards sustainable soil management in Europe.
Keywords: knowledge barriers; place-based practices; science-policy-practitioner nexus; soil challenges and threats; system approaches; divergent perspectives; EJP SOIL